RETRACTED: Public Libraries As Community Engagement Hub: An Analytical Study - A.V., Ramya; K.C., Abdul Majeed (Access: An International Journal of Nepal Library Association, 2025)
On 12th February 2026 the article “Public Libraries As Community Engagement Hub: An Analytical Study.” Access: An International Journal of Nepal Library Association, 4(1), 104–114, https://doi.org/10.3126/access.v4i1.88812 was retracted. The principal author made a formal request for the retraction because the article had already been published in South India Journal of Social Sciences, 23(2), 26-30. https://doi.org/10.62656/SIJSS.v23i2.1778